Yeast Protein Kinases and the RHO1 Exchange Factor TUS1 Are Novel Components of the Cell Integrity Pathway in Yeast - Schmelzle, Tobias (American Society for Microbiology, 2002)
The PKC1-associated mitogen-activated protein (MAP) kinase pathway of Saccharomyces cerevisiae regulates cell integrity by controlling the actin cytoskeleton and cell wall synthesis. Activation of PKC1 occurs via the GTPase RHO1 and the kinase pair PKH1 and PKH2. Here we report that YPK1 and YPK2, an essential pair of homologous kinases and proposed downstream effectors of PKH and sphingolipids, are also regulators of the PKC1-controlled MAP kinase cascade. ypk mutants display random distribution of the actin cytoskeleton and severely reduced activation of the MAP kinase MPK1. Upregulation of the RHO1 GTPase switch or the PKC1 effector MAP kinase pathway suppresses the growth and actin defects of ypk cells. ypk lethality is also suppressed by overexpression of an uncharacterized gene termed TUS1. TUS1 is a novel RHO1 exchange factor that contributes to cell wall integrity-mediated modulation of RHO1 activity. Thus, TUS1 and the YPKs add to the growing complexity of RHO1 and PKC1 regulation in the cell integrity signaling pathway. Furthermore, our findings suggest that the YPKs are a missing link between sphingolipid signaling and the cell integrity pathway.